The Role of Agroforestry for Climate Change Adaptation and Mitigation - Didik Utomo Pribadi; Moch. Sodiq; Fadila Suryandika (Future Science, 2023)
The agroforestry system is a plant cultivation technology as a form of adaptation and mitigation to climate change. The role of agroforestry in adapting to climate change through the translocation or transfer of germplasm approach, local genetic adaptation, and plasticization of individual species. The role of agroforestry in mitigating climate change through carbon sequestration, stock protection, and utilization of renewable energy.